2012
DOI: 10.33549/physiolres.932163
|View full text |Cite
|
Sign up to set email alerts
|

Preadipocyte Factor-1 Concentrations in Patients With Anorexia Nervosa: the Influence of Partial Realimentation

Abstract: Preadipocyte factor-1 (Pref-1) is a member of epidermal growth-factor like family of proteins that regulates adipocyte and osteoblast differentiation. Experimental studies suggest that circulating Pref-1 levels may be also involved in the regulation of lipid and glucose metabolism and energy homeostasis. We hypothesized that alterations in Pref-1 levels may contribute to the ethiopathogenesis of anorexia nervosa or its underlying metabolic abnormalities. We measured Pref-1 concentrations and other hormonal, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Twenty-nine studies (47%) investigated inpatients, 8 (13%) outpatients, 2 (3%) a mixture of both, and 23 studies (37%) did not specify the recruitment or patientsetting. Twenty-seven studies (44%) comprised collection of blood samples after a fasting period, whereas only six studies (10%) specified the fasting period (Bredella et al, 2012;DiVasta et al, 2011;Dostálová, Sedlácková, Papezová, Nedvídková, & Haluzík, 2009;Estour et al, 2017;Kaválková et al, 2012;Prioletta et al, 2011). One study (3%) did not specify whether analyses were performed using plasma or serum blood (Weinbrenner et al, 2004).…”
Section: Results Of the Search And Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-nine studies (47%) investigated inpatients, 8 (13%) outpatients, 2 (3%) a mixture of both, and 23 studies (37%) did not specify the recruitment or patientsetting. Twenty-seven studies (44%) comprised collection of blood samples after a fasting period, whereas only six studies (10%) specified the fasting period (Bredella et al, 2012;DiVasta et al, 2011;Dostálová, Sedlácková, Papezová, Nedvídková, & Haluzík, 2009;Estour et al, 2017;Kaválková et al, 2012;Prioletta et al, 2011). One study (3%) did not specify whether analyses were performed using plasma or serum blood (Weinbrenner et al, 2004).…”
Section: Results Of the Search And Selection Of Studiesmentioning
confidence: 99%
“…One study (3%) did not specify whether analyses were performed using plasma or serum blood (Weinbrenner et al, 2004). Seventeen studies (27%) sampled regular menstruating participants during the follicular phase of their cycle (de Alvaro et al, 2007;Dostálová et al, 2009;Estour et al, 2017;Galusca et al, 2015;Germain et al, 2010Germain et al, , 2007Germain et al, , 2016Grinspoon et al, 2001;Kaválková et al, 2012;Kirchengast & Huber, 2004;Mayer et al, 2005Mayer et al, , 2009Nakai, Hamagaki, Takagi, Taniguchi, & Kurimoto, 1999;Prioletta et al, 2011;Scalfi et. al, 2002;Weinbrenner et al, 2004), whereas 14 studies (23%) did not provide details about the cycle phase (Bachmann et al, 2014;Bredella et al, 2012;Delporte, Brichard, Hermans, Beguin, & Lambert, 2003;DiVasta et al, 2011;Fazeli et al, 2010;Fernández-Soto et al, 2013;Germain et al, 2010;Gniuli, Liverani, Capristo, Greco, & Mingrone, 2001;Grinspoon et al, 1996;Guo, Jiang, Liao, Liu, & He, 2013;Haas et al, 2005;Karczewska-Kupczewska et al, 2010;Maïmoun et al, 2018;Mörkl et al, 2017;Nakahara et al, 2007;Rigaud, Boulier, Tallonneau, Brindisi, & Rozen, 2010;Tagami et al, 2004;Tanaka et al, 2003).…”
Section: Results Of the Search And Selection Of Studiesmentioning
confidence: 99%
“…Subjects were free of any medication for more than 3 months prior to the beginning of the study. The realimentation program has been described in more detail previously 18 . During the realimentation period (46 ± 2 days) the daily energy content was 9630 kJ/day.…”
Section: Methodsmentioning
confidence: 99%
“…1-year follow-up, weight-recovered AN, and recovered AN). We summarized those by using the term "after partial weight restoration" (see of the studies (Crisp et al, 1968;Heilbronn et al, 2007;Kavalkova et al, 2012;Misra et al, 2006;Shih et al, 2016;Umeki, 1988;Uzum et al, 2009). One of 17 (6%) studies reported that the lipid profile normalized after weight gain but numerical values were not available (Rigaud et al, 2009).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…In longitudinal studies of individuals with AN where lipid profiles normalize after weight restoration, the evidence points towards the effects of starvation as the reason behind the increased lipid concentrations (Rigaud et al, 2009), whereas studies in which there are no significant differences before and after weight restoration may suggest a more fundamental lipid dysregulation (Crisp et al, 1968;Heilbronn et al, 2007;Kavalkova et al, 2012;Misra et al, 2006;Shih et al, 2016;Umeki, 1988;Uzum et al, 2009).…”
Section: Random Effects Modelmentioning
confidence: 99%